1989
DOI: 10.1111/j.1365-2125.1989.tb05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cyclosporin: influence of rate‐duration profile of an intravenous infusion in renal transplant patients.

Abstract: 1 The pharmacokinetics of cyclosporin were studied in six renal transplant patients, following intravenous administration of 5 mg kg-' infused over 3, 6 and 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…As stated by Gupta and associates, rate of infusion can influence pharmacokinetics of CsA and consequently be associated with (peak) concentration-dependent adverse effects. 7 This fact has also been confirmed in animal studies. 8 Some studies have shown that nephrotoxicity, neurotoxicity, hypertension, and metabolic abnormalities from CsA could be dose or concentration dependent.…”
Section: Discussionmentioning
confidence: 59%
“…As stated by Gupta and associates, rate of infusion can influence pharmacokinetics of CsA and consequently be associated with (peak) concentration-dependent adverse effects. 7 This fact has also been confirmed in animal studies. 8 Some studies have shown that nephrotoxicity, neurotoxicity, hypertension, and metabolic abnormalities from CsA could be dose or concentration dependent.…”
Section: Discussionmentioning
confidence: 59%
“…Blood samples to measure serum creatinine, total bilirubin, and cyclosporine levels were obtained at baseline (8 days before), 1 day before, and days 3,6,10,13,17,20,24, and 27 after allogeneic bone marrow transplantation. Samples were obtained at the same time each day immediately prior to initiation of the cyclosporine infusion.…”
Section: Study Protocolmentioning
confidence: 99%